Enhancement of Arctic storm activity in relation to permafrost degradation in eastern Siberia. (3rd February 2016) - Iijima, Yoshihiro; Nakamura, Tetsu; Park, Hotaek; Tachibana, Yoshihiro; Fedorov, Alexander N.
ABSTRACT: In the last decade, increases in both soil temperature and active layer thickness have been observed in the central Lena River basin, an area located in the centre of continuous permafrost in the Eurasian continent. Increased soil temperatures have been accompanied by corresponding increases in soil moisture within the active layer at many sites throughout the region. These underground hydro‐thermal changes are believed to be primarily due to perennially wet climate conditions, rather than the atmospheric warming alone that has resulted in abnormally large amounts of winter snow accumulation and late summer rainfall in the Lena River basin. This study aimed to clarify the linkage between atmospheric and land surface variations in regions of continuous permafrost in eastern Siberia based on in situ observation and atmospheric climatic data analyses. These wet conditions in 2004–2008 were likely caused by the enhancement of cyclones over the Arctic Ocean and eastward propagation of storm activity during late summer and early winter. Water vapour flux was enhanced in conjunction with the manifestation of precipitation in eastern Siberia. As a result, consecutive positive anomalies of winter snow accumulation and precipitation during the subsequent summers effectively humidified land surfaces in the permafrost region from 2005 onwards, which resulted in abrupt soil warming and wetting of both the active layer and the upper part of the permafrost. The positive effects on increasing soil temperatures of both snowfall in winter and rainfall in summer have been observed in eastern Siberia since the 1990s, and have also been demonstrated through land surface simulation. Results of these hydro‐climatic changes indicated that the near‐surface permafrost in eastern Siberia is vulnerable to the climatic conditions that have arisen due to the acceleration of the hydrological cycle that has resulted from the aforementioned period of warming.